Onchocerciasis: Current knowledge and future goals - Frallonardo, Luisa; Di Gennaro, Francesco; Panico, Gianfranco Giorgio; Novara, Roberta; Pallara, Elisabetta; Cotugno, Sergio; Guido, Giacomo; De Vita, Elda; Ricciardi, Aurelia; Totaro, Valentina; Camporeale, Michele; De Iaco, Giuseppina; et al. (Frontiers in Tropical Diseases, 2022)
Human Onchocerciasis, caused by infection by the filarial nematode Onchocerca volvulus, is a neglected public health disease that affects millions of people in the endemic regions of sub-Saharan Africa and Latin America. It is also called river blindness because the Blackflies that transmit infection breeds in rapidly flowing fresh water streams and rivers. This review features state-of-the-art data on the parasite, its endobacteria Wolbachia, the prevalence of the infection and its geographical distribution, its diagnostics, the interaction between the parasite and its host, and the pathology of Onchocerciasis. By development and optimization of the control measures, transmission by the vector has been interrupted in foci of countries in the Americas (Colombia, Ecuador, Mexico, and Guatemala)and inSudan, followed by Onchocerciasis eliminations. The current state and future perspectives for vector control and elimination strategy are described.